Writing a watertight thesis a guide to successful structure and defence - Bottery, Mike (Bloomsbury Academic, 2020)
Writing a doctoral thesis can be an arduous and confusing process. This book provides a clear framework for developing a sound structure for your thesis, using a simple approach to make it watertight, defensible and clear. Bottery and Wright draw on their extensive experience of supervising and examining numerous doctorates from an internationally diverse and multicultural student body both in the UK and overseas, and include examples of how successful theses have been made watertight along with exercises to enable readers to do the same thing to their own thesis. The authors demonstrate how the key to making a thesis watertight lies in selecting the central research question and the sub-research questions that together collectively answer this main one. If these questions are well formulated the thesis can be defended successfully against criticism on structural grounds - a major part of the battle. Including chapters on the viva process, strength-testing your thesis and essential preparation for writing up your research, this is the resource for anyone looking to produce a well-structured, watertight piece of research.